Altered somatosensory processing in secondary trigeminal neuralgia: A case report - Noboru Noma; Kana Ozasa; Andrew Young (Wolters Kluwer Medknow Publications, 2021)
Secondary trigeminal neuralgia might be very rarely preceded by trigeminal neuropathic pain. The patient, in this case, presented with paroxysmal pain in the left mandible and numbness of the lower lip and tongue. Sensory testing of these areas revealed cold and heat hyperalgesia and mechanical hyposensitivity in the mandibular region. Magnetic resonance imaging showed a mass in the left cerebellopontine angle. The patient was prescribed systemic mirogabalin (2.5 mg/day), which provided some relief until the tumor was removed. The histopathological diagnosis was an epidermoid tumor. This article discusses the clinical characteristics and sensory testing findings that distinguish secondary trigeminal neuralgia from trigeminal neuropathic pain based on the International Classification of Orofacial Pain.